2013
DOI: 10.3168/jds.2012-6100
|View full text |Cite
|
Sign up to set email alerts
|

Jersey calf performance in response to high-protein, high-fat liquid feeds with varied fatty acid profiles: Blood metabolites and liver gene expression

Abstract: Most available Jersey calf milk replacers (CMR) use edible lard as the primary fat source, which lacks medium-chain fatty acids (MCFA). However, Jersey cow milk consists of over 10% MCFA. The objective of this trial was to determine whether altering the fatty acid profile of CMR by increasing the amount of MCFA would alter liver lipid infiltration, liver gene expression, and blood metabolites when fed to Jersey calves. Fifty Jersey calves were fed 1 of 4 diets: pasteurized saleable whole milk (pSWM) from Jerse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Also, MCFA MR contained slightly less fat (% of DM) compared with CON, which could be influencing the lower serum NEFA in MCFA calves. A prior study conducted using Jersey calves observed that fasting serum NEFA concentrations decreased as dietary MCFA increased (Swank et al, 2013), which is in agreeance with the current study. Another potential contributor for reduced NEFA concentrations at d 42 for MCFA calves is the numerical increase in starter intake for these calves.…”
Section: Discussionsupporting
confidence: 93%
“…Also, MCFA MR contained slightly less fat (% of DM) compared with CON, which could be influencing the lower serum NEFA in MCFA calves. A prior study conducted using Jersey calves observed that fasting serum NEFA concentrations decreased as dietary MCFA increased (Swank et al, 2013), which is in agreeance with the current study. Another potential contributor for reduced NEFA concentrations at d 42 for MCFA calves is the numerical increase in starter intake for these calves.…”
Section: Discussionsupporting
confidence: 93%
“…The ether extract and crude protein content of the MR sampled are below those observed in MR commercialized in countries with a more developed dairy industry (Table 1). According to Swank et al (2013), feeding MR with CP and EE content lower than 20%, as most of the products sampled in this study, may negatively affect dairy calves' performance. Similarly, Bascom et al (2007) showed that weight gain and feed efficiency are lower for calves fed with milk replacer with CP and EE of 20%, as compared to animals fed whole milk or replacer with higher CP associated with EE lower than 20 %.…”
Section: Resultsmentioning
confidence: 94%
“…Female body is bearing the heaviest stress during pregnancy -all systems and organs endure overload not only during pregnancy, but also after -during calving and ongoing lactation [2,13]. Dairy yield and the calf condition depend on health and wellbeing of the cow [15]. That is why it is essential to pay attention to the cows and heifers during the last trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%